Potensi Bioenergi Dari Pengolahan Limbah Peternakan Dan Sampah Organik Di Kabupaten Banyuwangi - Kartini, Audiananti Meganandi; Ilminnafik, Nasrul (Jurnal Kendali Teknik dan Sains, 2024)
Banyuwangi Regency has an area of ​​5,782.5 km2, which is divided into 25 sub-districts and 217 villages/sub-districts with a population in 2021 reaching approximately 1,718,462 people. Based on BPS data from Banyuwangi Regency in 2020, it shows that the total livestock population is 3,130,769. These types of livestock consist of four-legged animals such as cows, buffalo, horses, goats, sheep, pigs and poultry such as chickens. The aim of this research is to find out the potential electrical energy obtained from livestock manure and to measure and identify the potential electrical energy from waste processing which is developed into a biomass power plant in Banyuwangi Regency. The research method in writing this article is descriptive quantitative, the data was obtained from literature studies. Biogas potential from the livestock sector in Banyuwangi Regency is considered high with a total of 297,680 m3 of biogas that can be produced. Meanwhile, the total weight of waste generated in Banyuwangi Regency is 572,261 kg/day. So it was found that the total bioenergy produced from livestock manure in Banyuwangi Regency reached 297,681 m3, while the total electrical energy produced from organic waste in Banyuwangi Regency reached 414,061 kWh per day.